Pengaruh Kandungan Dan Ukuran Serbuk Genteng Sokka Terhadap Ketahanan Bakar Komposit Geopolimer - Diharjo, Kuncoro; Kusharjanta, Bambang; P Tarigan, Roy Aries; Andhika, Albert Raga (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
The objective of this research is to investigate the effect of particle content and grain size of Sokka roof tile powder on the burning endurance of the composite of Sokka roof tile powder - ripoxy R-802.The materials used were a Sokka roof tile powder (SGS), ripoxy R-802 resin, MEKPO catalyst and P-EX promotor. The Sokka roof tile powder was generated from the rejected Sokka roof tile which was crushed into powder. The powder was sieved to result in three size variances, which were mesh 80 retained in mesh 100 (177Î¼m-149Î¼m), mesh 150 retained in mesh 200 (99Î¼m-74Î¼m), and breaking away from mesh 200 (â‰¤74Î¼m). Prior to getting mixed with the resin, SGS was heated in an oven for 45 minutes in the temperature of 105oC. Afterwards, the powder was mixed with ripoxy R-802 resin for 3 minutes. The variances of SGS content were determined to be 10%, 20%, 30% and 40% composition. Making composite was conducted by press mould. Fixed composites was given post curing treatment in the temperatures of 80oC for 120 minutes. The burning testing on the composite was conducted on the basis of the standard of ASTM D-635. The indicator of burning endurance was determined by the data of time of burning (TOB) and rate of burning (ROB). The TOB resulted from the time of ignition and the ROB resulted from the time of fire propagation time in the composite. The results of this research are as follows: (1) the addition of SGS can improve the burning endurance of the composite of SGS-ripoxy R-802 as indicated by the increase in the TOB but the decrease of ROB due to the addition of the content of SGS; (2) the small size of the particle of SGS can increase the burning endurance of the composite of SGS-ripoxy R-802 as signified by the increase in the TOB but the decrease in the ROB due to the small size of the particle of SGS which breaks away from mesh 200 (â‰¤74Î¼m).